Total thyroidectomy Results of 50 consecutive cases - Botta, Fernando; Delgado, Bolívar; Belloso, Rogelio (Cirugía del Uruguay, 1996)
The authors present the results of 50 consecutive total thyroidectomies (TT), showing its feasability with mínimum or no morbility under certain conditions. Other authors' results are compared, pointing out common features, such as surgical technique, and the authors' special interest in this surgica/ area